Mineralogical Characteristics of Flash Flood Sediments in Masamba River Using X-Ray Diffraction (XRD) Method - Amardika; Rahmaniah; Said L, Muh (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2025)
This study was conducted to analyse the sediment characteristics transported by flooding in the Masamba River, North Luwu Regency, using the X-Ray Diffraction (XRD) method. The characteristics analysed include the crystal structure and mineral content of the sediment transported after the flash flood on 13 July 2020. Sampling was carried out randomly at three points along the Masamba Riverbank at depths of 0 cm (surface), 50 cm, and 100 cm. The results of the study showed that the crystal structure of the sediment varied greatly at each point. At point A, the crystal structure at depths of 0 cm and 50 cm was Orthorhombic, while at a depth of 100 cm it was Monoclinic. At point B, all samples at depths of 0 cm, 50 cm, and 100 cm exhibited a Trigonal (hexagonal-axes) crystal structure. Meanwhile, at point C, the crystal structure at a depth of 0 cm was Triclinic (anorthic), whereas at depths of 50 cm and 100 cm it was Orthorhombic. Regarding mineral content, at point A, sediments at depths of 0 cm and 50 cm contained Titanium(IV) Oxide Phosphate (O20P4Ti5), while at a depth of 100 cm they contained (C20Cl10N6). At point B, all samples (0 cm, 50 cm, and 100 cm) were dominated by Quartz (O2Si). At point C, sediments at a depth of 0 cm contained (B3H3N12), sediments at a depth of 50 cm contained (Cs3F6Ga), and sediments at a depth of 100 cm contained (Bi38Mo7O78). These results indicate that the flash flood had a significant impact on the sediment characteristics in the Masamba River.